Analysis of the Public Prosecution Proposal for the mediation of conflicts in schools: conceptions of democratic management and dialogue - Gomes, Alessandro; Francisco, Marcos Vinicius [UNESP] (Univ Nove Julho, 2019)
In this paper, the objective was to analyze the conception of democratic management and dialogue present in the Proposal of the Public Prosecutor for the mediation of conflicts in Brazilian schools. The research is qualitative in nature, and documentary analysis was used as a methodological procedure. The analyzes were established from the document Dialogues and Conflict Mediation in Schools: Practical Guide for Educators, promoted by the National Council of the Public Prosecution, a body outside the school. The main results pointed to some contradictions in the Guide, the proposed dialogue isn't suitable for the implementation of a democratic school management. When teachers and the school receive a document ready, in order to act in situations that promote violence, its capabilities for autonomy, another basic principle for the implementation of democratic management.
Keywords: Democratic School Management; Dialogue; Conflict Mediation in Schools